Power to the people? The limits of equality-based involvement in managing strategic change - MACK, Daniel Z. (Institutional Knowledge at Singapore Management University, 2020)
Existing research has highlighted the importance of involving a wide representation of organizational members in the strategic change process to manage it effectively. We conducted a real-time inductive study of a strategic change at an organization in the hotel industry. Our findings suggest that the equality-based involvement – designed to promote equal opportunities for voice among employees – unintendedly undermined the implementation of strategic change. Although wide organizational involvement provided frontline employees with greater voice and autonomy, it also instilled greater fear in middle managers due to more escalating complaints to top management and newly created constraints in middle managers’ supervisory tasks. Consequently, top management had to devote unexpected significant efforts to address escalated issues rather than improving the organization’s productivity. Our study contributes to the literature on strategic change by highlighting the limits of equality-based involvement practices when organizational members have asymmetric motivations and covert emotional reactions.